Context dependent variation in associations between grasses and fungal symbionts - Kauppinen, M. (Miia) (Oulun yliopisto, 2017)
Abstract Most plants form symbiotic associations with various fungi in natural ecosystems. Traditionally, many of these associations are viewed as mutually beneficial, but recent studies show that symbiotic interactions can be complex and labile. I studied the variability of interactions between grasses and fungi, using root-associated fungi and foliar endophytes in grasses as study systems. First, I studied experimentally how root-associated fungi colonize their host grasses in different natural and artificial conditions. I then investigated experimentally how foliar endophytes affect their host grasses, and whether the endophyte contributes to the host’s adaptation to local and/or foreign habitats. Finally, I reviewed the current use of foliar endophytes in agriculture, with a particular focus on Europe, and critically considered their potential for practices beyond agriculture. I found root fungi to be common, but different types of root fungi had contrasting colonization patterns in natural environments. However, I found that grasses lose almost all of their root fungi in controlled and more favourable conditions, indicating that the associations are fairly loose and conditional to environmental context. My results also showed that foliar endophytes affected the host’s performance in varying ways, depending on plant origin and experimental country, indicating that the associations were context dependent and could represent conditional mutualism. I also found that endophytes contribute to plant adaptation only weakly, but that the grasses were clearly locally adapted to their sites of origin, especially in regard to reproduction. However, the grasses of subalpine origin performed well vegetatively also in Northern Finland, suggesting that they may have high adaptive potential under changing climates. The literary review showed that foliar endophytes are successfully used in agriculture, e.g. in the USA and New Zealand, and that they possess the potential for several practical applications. However, the ...